TINJAUAN MASLAHAH TERHADAP POLITIK HUKUM PENETAPAN BATAS MINIMAL USIA PERKAWINAN DALAM UNDANG-UNDANG NOMOR 16 TAHUN 2019 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Efrinaldi, Efrinaldi; Fahimah, Iim; Shafra, Shafra; Billah, Yusuf Ridho; Putra, Andi Eka (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2022)
Law Number 16 of 2019 Amendments to Law Number 1 of 1974 concerning Marriage raise the minimum age for marriage for both men and women to be 19 years old. This was not just an equalization of the minimum age for men and women, but there were government legal politics to improve the quality of Indonesian marriages. The focus of this research was a review of the problems of the legal politics of the minimum age limit for marriage in Law Number 16 of 2019? This study concludes that the legal politics of determining the minimum age for marriage in Indonesia in the Law of the Republic of Indonesia Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage with the principles of equality and justice; non-discrimination; the state's obligation to actively protect and ensure the fulfillment of human rights and freedoms; the best interests of the child; the right to life which guarantees that every child has the right to live, develop and carry on their lives and the state was obliged to guarantee it and fulfill the rights of the child, respect for the opinion of the child; orderly and legally certainty; in line with maslahah which was the goal of Islamic law related to maintaining offspring (hifz an-nasl).